Evaluasi Program Gerakan Indonesia Sadar Administrasi Kependudukan (GISA) Di Dinas Kependudukan Dan Pencatatan Sipil Kota Sibolga - Lucyana Virgi Sonia Limbong; Tunggul Sihombing (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
Program evaluation is a unit of activity that aims to collect information that implements a policy, takes place in a continuous process, and occurs in an organization that involves a group of people for decision making. Program evaluation aims to determine the achievement of program objectives implemented. Based on the Instruction of the Ministry of Home Affairs of the Republic of Indonesia Number 470/837/SJ concerning the Population Administration Movement, the main objective of this movement is to increase public awareness in the field of population administration towards an orderly society, an effective and efficient government and a competitive state. Regarding the GISA program in Sibolga City, it was found that there were still people who did not have an orderly population administration, the target of the GISA program did not know the program's objectives, the programs carried out were not targeted at the community and there was no increase in document ownership from 2019 to 2020 in the administration of KIA ownership. For this reason, this study will identify and describe in detail the evaluation of the GISA Program at the Population and Civil Registration Office of Sibolga City. This study uses a descriptive research method with a qualitative approach. Data collection techniques used are interviews, observations and documentation related to the evaluation of the GISA program at the Population and Civil Registration Office of Sibolga City. The data obtained were analyzed qualitatively by examining all the collected data, studying the data, and compiling the data obtained using the approach proposed by D. Stufflebeam using the CIPP evaluation model, namely, Context, Input, Process and Product. Through this research, it is known that the evaluation of the GISA program at the Population and Civil Registration Office of Sibolga City on the context dimension of the GISA program can be found that there are still people who are not aware of the importance of ownership of population documents so that the necessary needs are not met. The input dimension for the evaluation of the GISA program found was that the facilities and infrastructure were not optimal enough to fulfill the implementation of the GISA program, so that the technical implementation of document formation was not carried out properly. In the Process dimension, there are still people who do not know the GISA program about the importance of ownership of population documents and the schedule of activities is not carried out properly due to the Covid-19 pandemic. The Product Dimensions found to have the effect of this program have not been conveyed to the community as a whole.